The role of psychodynamic psychotherapy for the older adult – two contrasting cases. (December 2019) - Jeyasingam, Neil
Objective: To outline the successful psychotherapeutic intervention of two older patients. Conclusion: Psychodynamic principles should be considered more readily in the treatment of older people.